2021
DOI: 10.1093/molbev/msab047
|View full text |Cite
|
Sign up to set email alerts
|

Biases in demographic modelling affect our understanding of recent divergence

Abstract: Testing among competing demographic models of divergence has become an important component of evolutionary research in model and non-model organisms. However, the effect of unaccounted demographic events on model choice and parameter estimation remains largely unexplored. Using extensive simulations, we demonstrate that under realistic divergence scenarios, failure to account for population size (Ne) changes in daughter and ancestral populations leads to strong biases in divergence time estimates as well as mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 90 publications
2
52
0
Order By: Relevance
“…Several factors (e.g. ancestral size changes and undetected bottlenecks, Momigliano et al, 2021;unac-counted gene flow from 'ghost' populations, Lynch & Sethuraman, 2019; low coverage or sequencing error, Gravel et al, 2011) could be contributing to discordance between our parameter estimates. We also note here that methodological approaches that fail to account for gene flow, such as SNAPP, can result in topological uncertainty (Thom et al, 2018), which could also be contributing to the observed discordance between our parameter estimates.…”
Section: Mosaic Genomes and The Role Of Introgressionmentioning
confidence: 96%
“…Several factors (e.g. ancestral size changes and undetected bottlenecks, Momigliano et al, 2021;unac-counted gene flow from 'ghost' populations, Lynch & Sethuraman, 2019; low coverage or sequencing error, Gravel et al, 2011) could be contributing to discordance between our parameter estimates. We also note here that methodological approaches that fail to account for gene flow, such as SNAPP, can result in topological uncertainty (Thom et al, 2018), which could also be contributing to the observed discordance between our parameter estimates.…”
Section: Mosaic Genomes and The Role Of Introgressionmentioning
confidence: 96%
“…Although results from dadi gave the greatest support to the two-epoch models of divergence in isolation followed by secondary contacts (Tables 1 and 2), if population expansions or bottlenecks have occurred, divergence time can be over-estimated and results can favour the secondary contact model (Momigliano, Florin, & Merila, 2021). As RAD datasets with de novo assemblies are prone to high error rates in low frequency SNP calling (Andrews, Good, Miller, Luikart, & Hohenlohe, 2016), we did not include singletons and doubletons in the analyses and thus were unable to accurately model population size changes and differentiate between the different migration scenarios (i.e ., ancient migration vs. continuous migration vs. secondary contact).…”
Section: Gene Flow Between Cryptic Taxa and Speciesmentioning
confidence: 92%
“…From another point of view, the correct choice of parameters is very important. Moreover, the experience of the scholar determines the amount of work involved in the research [48][49][50]. In Fig.…”
Section: Comprehensive Comparison Of the Algorithm With Local Input And Cross-station Inputmentioning
confidence: 99%